Dukungan Suami Dengan Kejadian Postpartum Blues Di Puskesmas Mumbulsari - Mobarokah, Fatihatul (Universitas Malahayati Bandar Lampung, 2023)
Background: Husband's support is the biggest factor in triggering post partum blues. This is because husband's support is an important coping strategy when experiencing stress and functions as a preventive strategy to reduce stress. Those who receive husband's support both emotionally, support and appreciation relatively do not show post partum symptoms. Objective: This study aims to analyze the relationship between husband's support and the incidence of postpartum blues. Method: This research is a cross-sectional study. Data was taken from medical records of mothers giving birth at the Mumbulsari Community Health Center, Mumbulsari District, Jember Regency. which was carried out from April 14 2022 to May 31 2022 with a population and sample of 33 mothers giving birth. The sampling technique used in this research is a saturated sample, namely the number of samples is the same as the population. Data collection includes editing, scoring, coding, tabulating, then the data is analyzed manually and by computer with the chi-square test. The tabulation results showed that the majority received good support from their husbands, 24 people (72.73%), the majority did not experience Postpartum Blues, 30 people (90.91%), Conclusion: There is a relationship between husband's support and the incidence of postpartum blues at the Mumbulsari Community Health Center, Mumbulsari District, Regency. Jember. with a value of ρ = 0.000 and OR 0.001. Suggestion: It is hoped that there will be an increase in the socialization of husband's support regarding the Postpartum Blues incident Keywords: Husband's support, Postpartum, Postpartum Blues ABSTRAK Latar belakang: Dukungan suami merupakan faktor terbesar dalam memicu kejadian post partum blues. Hal ini dikarenakan dukungan suami merupakan strategi koping penting pada saat mengalami stress dan berfungsi sebagai strategi preventif untuk mengurangi stress. Mereka yang mendapatkan dukungan suami baik secara emosional, support, penghargaan relatif tidak menunjukkan gejala post partum. Tujuan:Penelitian ini bertujuan untuk menganalisis hubungan antara dukungan suami dengan kejadian postpartum blues.metode: Penelitian ini termasuk penelitian crossectional. Data daimbil dari rekam medik ibu melahirkan di Puskesmas Mumbulsari Kecamatan Mumbulsari Kabupaten Jember. yang dilaksanakan pada tanggal 14 April 2022 sampai tanggal 31 Mei 2022 dengan jumlah populasi dan sampel sebanyak 33 orang ibu melahirkan. Tehnik sampling yang digunakan dalam penelitian ini adalah sampel jenuh yaitu jumlah sampel sama dengan jumlah populasi. Pegumpulan data meliputi editing, scoring, coding, tabulating, kemudian data dianasilis secara manula dan komputer dengan chi-square test. Hasil tabulasi diperoleh mayoritas mendapatkan dukungan baik dari suami sebanyak 24 orang (72,73%), mayoritas tidak mengalami Postpartum Blues sebanyak 30 orang (90,91%),Kesimpulan: ada Hubungan dukungan suami dengan kejadian postpartum blues di Puskesmas Mumbulsari Kecamatan Mumbulsari Kabupaten Jember. dengan nilai ρ = 0,000 dan OR 0,001. Saran:Diharapkan ada peningkatan sosialisasi dukungan suami dengan kejadian Postpartum Blues Kata Kunci : Dukungan suami, Postpartum,Postpartum Blues